5G-Smart Diabetes: Building Health Care Big Data Clouds for Individualized Diabetes Diagnosis - Mudda Mallikarjun; M Ambika; Kumar G. Ganesh; Choubey Shruti Bhargava (ITM Web of Conferences)
Using existing 5G technology, this program will keep tabs on diabetic patients’ wellbeing while keeping costs down. A lot of people nowadays are coping with diabetes because they made poor lifestyle choices or because they were too stressed out at work. Sadly, most individuals don’t notice anything is wrong until they have symptoms or receive a medical diagnosis; by then, the illness has already advanced a long distance, and there’s no way to discover it early. Type 1 and type 2 diabetes will exist separately. While hospitalization is required for type 2 diabetes, we may monitor patients with type 1 diabetes and inform them or their doctors of their progress. Nearly 8.5% of the world’s population is diabetic, and 422 million people throughout the world suffer from diabetesrelated problems. Type 2 diabetes mellitus accounts for around 90% of all occurrences, so keep that in mind [1]. As previously stated, this puts an even greater number of young individuals at risk for acquiring diabetes. Because diabetes affects health and the economy all across the world, there is an urgent need for better methods of preventing and treating the illness. A variety of factors, such as an unhealthy lifestyle, a vulnerable mental state, and high levels of stress from both work and society, can also contribute to the development of the illness. However, there are a number of problems with the present method of diabetes screening